(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2022)
Fish can be processed into various products, such as smoked fish. This product is unique, much in demand, and can extend the shelf life of fish. Traditionally processed smoked fish often does not meet the quality standards of smoked fish quality. Therefore, the efhilink fumigation device was developed. This study was conducted to compare the smoked tuna using traditional smoking and efhilink using corn cob smoked as fuel. This study obtained data that smoked tuna with efhilink has better quality than smoked tuna with traditional processing based on organoleptic quality parameters, carbon residue content, water content, and microbiological quality based on ALT values.